Eksplorasi Budaya Organisasi dan Pengaruhnya Terhadap Kinerja Karyawan: Studi Kualitatif di Perusahaan Startup - Albertus Aldo Nugroho; Sabina Siti Sholeha; Khresna Adityo Fathor (Universitas 45 Surabaya, 2025)
This study aims to understand the influence of organizational culture on employee performance in startup companies. Using a qualitative approach and case study design, research was conducted in several startups in Indonesia to explore employee perceptions and experiences regarding the dynamics of organizational culture. The findings show that a culture that supports innovation, open communication, and collaboration can increase work motivation and productivity. However, fast-paced work rhythms and unstable environments often trigger stress that impacts work-life balance. For this reason, companies need to combine an innovative culture with welfare policies to maintain employee performance.